Negotiating Consent in African Studies - Amanda Moller Rasmussen; Rune Larsen; Stig Jensen (Nordic Journal of African Studies)
Informed consent has been increasingly equated with standardized models and legal jargon. At Scandinavian universities, researchers are expected to adhere to European standardized models and institutional forms, necessitating documentable (preferably signed) consent from research participants. As Africanist researchers, we observe a growing dissonance between institutional expectations and fieldwork ethics and moralities. The field of African Studies has been pivotal in revealing how knowledge practices that are ostensibly universal are, in fact, products of deep-seated inequalities in higher education and knowledge production, perpetuating Western ideals of ethics. This introduction advocates for “customized consent” and introduces three concepts – consent contexts, consent interests, and consent mediators – to address and positively transform informed consent procedures and expectations.